2014
DOI: 10.1002/cncr.28628
|View full text |Cite
|
Sign up to set email alerts
|

Impact of timing and setting of palliative care referral on quality of end‐of‐life care in cancer patients

Abstract: Background Limited data is available on how the timing and setting of palliative care referral can affect end-of-life care. In this retrospective cohort study, we examined how the timing and setting of palliative care (PC) referral were associated with the quality of end-of-life care. Methods All adult patients residing in the Houston area who died of advanced cancer between 9/1/2009 and 2/28/2010 and had a PC consultation were included. We retrieved data on PC referral and quality of end-of-life care indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
302
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 357 publications
(330 citation statements)
references
References 26 publications
17
302
1
10
Order By: Relevance
“…We recently reported that early specialist palliative care referral was significantly associated with lower rates of emergency room visits, hospitalization, and intensive care unit admissions in the last 30 days of life, but not the rates of chemotherapy or targeted therapy use [19]. Taken together, these results suggest that the decision-making process regarding chemotherapy use at the EOL might be a separate construct from the delivery of palliative care.…”
Section: Discussionmentioning
confidence: 88%
“…We recently reported that early specialist palliative care referral was significantly associated with lower rates of emergency room visits, hospitalization, and intensive care unit admissions in the last 30 days of life, but not the rates of chemotherapy or targeted therapy use [19]. Taken together, these results suggest that the decision-making process regarding chemotherapy use at the EOL might be a separate construct from the delivery of palliative care.…”
Section: Discussionmentioning
confidence: 88%
“…Recognizing the significant supportive care needs among cancer patients and the role that palliative care plays in addressing these needs [1][2][3][4], multiple national and international professional organizations have called for increased integration of oncology and palliative care [5][6][7][8]. Since 2004, the European Society for Medical Oncology (EMSO) offered an incentive program of 'ESMO designated centers of integrated oncology and palliative care' based on 13 criteria that focused on the palliative carerelated processes, education, and research; however, these criteria did not explicitly include formal clinical structures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the model that has received the greatest attention and endorsement, in particular, for cancer centers, is simultaneous care by specialized palliative care in an outpatient setting [13,15,16]. This model was used in two randomized controlled trials (RCTs) demonstrating the benefits of EPC and was also supported by the results of nonrandomized prospective and retrospective studies [17][18][19]. Although this model has been examined qualitatively by a review of the electronic medical records of patients receiving EPC [20] and by interviewing oncologists and palliative care physicians [21,22], the opinions of patients and caregivers regarding this model of care have not been sought.…”
Section: Introductionmentioning
confidence: 99%